A busca por cidadania dos povo indígenas com base no socioambientalismo e no pluralismo jurídico: uma análise da conflituosidade em Novo Airão/Amazonas - Figueredo, Vaancklin dos Santos (2011)
This is the conflituosidade existing in the municipality of Novo Airão, within the State of Amazonas, which decades ago were only lands inhabited by indigenous peoples and Maroons and, after the creation of Indian Lands Atroari and Jau National Park created an overlap Rights that were regulated and thereby obtained the demarcation of land with the creation of the Jau National Park and the demarcation of land for Atroari. In contrast, the recognition of the original right of Indians to their lands traditionally occupied and the creation of the Jau National Park, caused great conflituosidade in the region with the expulsion of hundreds of families who lived in areas of the Jau National Park, these families, mostly part of the maroon communities. Currently, permanently defined areas of enjoyment Atroari and specified as Full Protection with the Jau National Park, created new conflict in the region, because many families expelled from the Jau National Park began to live on its periphery, thus causing new conflituosidade as part of traditional population continued its secular way of life in surrounding areas between indigenous lands and conservation units, but their way of life and survival as a group has been sapped, because some of the access routes to regions and municipalities that are within the district boundaries of indigenous lands Atroari or Jau National Park, causing the immediate effect of the punishment of those communities, with the application of coercive measures, such as administrative fines, lawsuits and seizure raw material obtained from areas not belonging to Atroari and Jau National Park. The dissertation starts focusing on the conflict to such existing contextualizing the issue within the broader aspects in relation to quilombola drives, nature conservation and the original right of Indians to their lands traditionally occupied, and then far be- will be a discussion on the institution of slavery in Brazil, the most important principles of environmental law for this dissertation and an explanation of territories and ethnographic research. Finally, it will hold a discussion on legal pluralism and conflict resolution in New Airão, focusing on the territorial rights of indigenous and traditional populations, overlapping areas considered while indigenous lands and conservation units and a proposed use of the Institute of servitude in Units of Nature Conservation for Sustainable Development - Full Protection Areas, conservation areas, these, adjacent to areas subject to dispute, but also to promote the "settlement" of the Maroons, showing the positions entered into on the subject and if there is major understandings about the superposition of these important standards. Keywords: Indigenous Lands. Units of Nature Conservation. Conflituosidade New Airão / Amazon. Traditional Populations.